Mechanism and capacities of reducing ecological cost through rice–duck cultivation. (27th June 2013) - Long, Pan; Huang, Huang; Liao, Xiaolan; Fu, Zhiqiang; Zheng, Huabin; Chen, Aiwu; Chen, Can
Abstract: Background: Rice–duck cultivation is the essence of Chinese traditional agriculture. A scientific assessment of the mechanism and its capacity is of theoretical significance and practical value in improving modern agricultural technology . Results: The duck's secretions, excreta and their treading, pecking and predation decrease the occurrence of plant diseases, pests and weeds, enrich species diversity and improve the field environment. The rice–duck intergrowth system effectively prevents rice planthoppers and rice leafhoppers. The control effects can be up to 98.47% and 100% respectively; it also has effects on the control of Chilo suppressalis, Tryporyza incertulas and the rice leafrollers. Notable control results are found on sheath blight, while the effects on other diseases are about 50%. Harm from weeds is placed under primary control; prevention of weeds is sequenced by broadleaf weeds > sedge weeds > Gramineae weeds. Contents of soil organic matter, N, P and K are improved by the system; nutrient utilization is accelerated, resulting in decreased fertilizer application. Greenhouse gas emissions are reduced by 1–2% and duck fodder is saved in this system. There is also an obvious economic benefit . Conclusion: Compared to conventional rice cultivation, rice–duck cultivation shows great benefits to ecologic cost and economic income. © 2013 The Authors. Journal of the Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry